Interpersonal Communication Skills of Teachers and Students: Building a Foundation for Meaningful Learning - Sukardi, Ni Wayan; Wastawa, I Wayan; Mantra, Ida Bagus Nyoman (PT. Riset Press International, 2025)
Interpersonal communication is one of the elements of communication that is often carried out by humans, not just to provide information to each other but also as a means to familiarize fellow human beings so that a sense arises to give each additional attention, motivation, pleasure so that they can help someone to tell their problems. This study aims to describe the interpersonal communication skills of teachers and students in the learning process and the obstacles encountered in interpersonal communication at school. The research method used is qualitative research, where data was collected through interviews and field observations. This research found that many teachers still faced various obstacles in communication and interpersonal relationships in the learning process, but various factors caused these obstacles. However, the barriers encountered can be solved with good communication. This study implies that stakeholders of educational institutions need to hold various training sessions so that teachers have good interpersonal communication skills.